Communication Privacy Management in Generation Z Men Who Experienced Fatherless - Adelya Oktafia Arda; Sumardjijati (Informasi, 2026)
The research was conducted due to the fatherless phenomenon, which influences the formation of personal information management in interpersonal relationships among Generation Z men. The absence of a father figure causes individuals to have to build personal boundaries independently through personal relationship experiences. This aims to determine how Generation Z men who have lost their father figure manage communication privacy in order to manage personal information in their interpersonal relationships. Descriptive qualitative methods, along with data collection, were used through in-depth interviews with Generation Z male respondents aged 20-25 years who had experienced the loss of a father, located in East Java. Through data analysis using the theory of communication privacy management by Sandra Petronio, the results of the study show that Generation Z men who live without fathers actively apply personal information management as a self-defense strategy independently, without the assistance of a father figure. This management includes personal rules based on trust and intimacy, strict risk considerations, and clear personal boundaries to prevent information leakage. Fatherlessness does not completely determine the management of privacy, but rather the experience of relationships, and the individual's adaptation process to this condition has a greater influence on the formation of communication privacy management.